(untitled) (American Journal of Islam and Society, 1994)
Shah Wali Allah’s (1703-63) ideas and profound intellectual legacy continue to atrract scholastic interest. Despite many works on his legacy, significant facets remain unknown. As his futuristic ideas hold great promise for modem and future Islamic thought, his works should be analyzed. We will focus on one such idea: his synthesis of reason, revelation, and empiricism. Building on evidence from an inductive survey of social phenomena to support the claims of revelation and staying within the doctrinal framework of revealed guidance, he constructs a universal social cultute paradigm and says that all Qur’anic injunctions and instructions of the Prophet are compatible with the demands of human nature. His view of the individual and human society is an integral facet of his philosophy of life and is one of the most original parts of his legacy. He sees life as a display of the grand divine scheme in natural order and Social organization. Although his exposition of humanity’s social development seems to be in the nature of a humanist and sometimes assumes the form of an empirical survey, his final conclusions confirm the fundamental postulates of religion. Some modem exponents of his social doctrines suggest that his ideas are not original and say that he might have taken them from Ibn Sin or Ibn Khaldiin. However, a totalist view of his framework of thought shows that this is an unwamted assertion ...